Gene Therapy for Neuropsychiatric Disorders: Potential Targets and Tools - Shahcheraghi, Seyed H.; Ayatollahi, Jamshid; Lotfi, Marzieh; Aljabali, Alaa A.A.; Al-Zoubi, Mazhar S.; Panda, Pritam K.; Mishra, Vijay; Satija, Saurabh; Charbe, Nitin B.; Serrano-Aroca, Ángel; Bahar, Bojlul; Takayama, Kazuo; et al. (CNS & Neurological Disorders - Drug Targets, 2023)
Neuropsychiatric disorders that affect the central nervous system cause considerable pressures on the health care system and have a substantial economic burden on modern societies. The present treatments based on available drugs are mostly ineffective and often costly. The molecular process of neuropsychiatric disorders is closely connected to modifying the genetic structures inherited or caused by damage, toxic chemicals, and some current diseases. Gene therapy is presently an experimental concept for neurological disorders. Clinical applications endeavor to alleviate the symptoms, reduce disease progression, and repair defective genes. Implementing gene therapy in inherited and acquired neurological illnesses entails the integration of several scientific disciplines, including virology, neurology, neurosurgery, molecular genetics, and immunology. Genetic manipulation has the power to minimize or cure illness by inducing genetic alterations at endogenous loci. Gene therapy that involves treating the disease by deleting, silencing, or editing defective genes and delivering genetic material to produce therapeutic molecules has excellent potential as a novel approach for treating neuropsychiatric disorders. With the recent advances in gene selection and vector design quality in targeted treatments, gene therapy could be an effective approach. This review article will investigate and report the newest and the most critical molecules and factors in neuropsychiatric disorder gene therapy. Different genome editing techniques available will be evaluated, and the review will highlight preclinical research of genome editing for neuropsychiatric disorders while also evaluating current limitations and potential strategies to overcome genome editing advancements.
Keywords: molecular targets